The SPN Network for Digital Audio Data Based on Elliptic Curve Over a Finite Field - Ijaz Khalid; Tariq Shah; Khalid Ali Almarhabi; Dawood Shah; Muhammad Asif; M. Usman Ashraf (IEEE Access, 2022)
The mathematical operation of the Elliptic Curve over the prime finite field is wildly used for secure data communication as it provides high security while utilizing the same size as the secret key. This manuscript presents a novel approach to the SPN (Substitution Permutation Network), for a new digital audio encryption scheme based on Mordell elliptic curve (MEC) over a finite prime field. The proposed scheme consists of a confusion and diffusion module. For the confusion module, the scheme initially generates $5× 5$ bijective S-boxes, which have never been applied in the present literature with good cryptographic properties. The generated S-box is then used parallel in the substitution module, which provides optimum confusion in the cipher data. For the diffusion property, the scheme generates pseudo-random number sequences used for block permutation and achieves the property of diffusion. The scheme has been thoroughly securitized against various attacks. The result shows the efficiency of the proposed algorithm over the existing schemes. In addition, the framework that is used to generate MEC points is based on the searching technique. Consequently, it significantly reduces the computational cost and enhances the scheme’s performance compared to the schemes presented in the literature.